Identification of a Conserved N-Terminal Sequence Involved in Transmembrane Signal Transduction in EnvZ - Waukau, Jill (American Society for Microbiology, 1999)
To determine whether N-terminal sequences are involved in the transmembrane signaling mechanism of EnvZ, the nucleotide sequences of envZ genes from several enteric bacteria were determined. Comparative analysis revealed that the amino acid sequence between Pro41 and Glu53 was highly conserved. To further analyze the role of the conserved sequence, envZ of Escherichia coli was subjected to random PCR mutagenesis and mutant alleles that produced a high-osmolarity phenotype, in which ompF was repressed, were isolated. The mutations identified clustered within, as well as adjacent to, the Pro41-to-Glu53 sequence. These findings suggest that the conserved Pro41-to-Glu53 sequence is involved in the signal transduction mechanism of EnvZ.